PEMBENTUKAN ANTI-AUTOMORFISMA PADA GELANGGANG OPERATOR DIFERENSIAL - Amir, Amir Kamal (MATEMATIKA, 2011)
﻿﻿. Let R be any ring with identity 1, be an endomorphism of R and be a left -derivation. The skew polynomial ring over R in an indeterminate x, denoted by , is the set of polynomials where with multiplication rule for all For the skew polynomial ring is written as and is called differential operator ring. In this paper will be constructed anti-automorphism on this ring, i.e., .